Visitor Perspectives on Alternative Parking Management Strategies: Implications for Meech Lake Parking Access and Visitor Use Management in Gatineau Park - Padvaiskas, Ashley V. (Université d'Ottawa | University of Ottawa, 2024)
Parks and protected areas often operate under a dual mandate, such that their management aims to conserve the natural environment while providing quality recreational opportunities for visitor enjoyment. Unfortunately, growing visitation trends have created complex managerial challenges when attempting to balance conservation goals with conflicting visitor demands across some of the most highly visited parks across Canada, including Gatineau Park. While even minimal levels of recreational use in an area can impose substantial environmental and social impacts, growing visitor densities at popular destinations in Gatineau Park, including Meech Lake, are likely to continue to strain managerial efforts put forth to restore the ecological integrity of the park and provide desired positive visitor experiences. This paper, based on a review of existing literature and various case studies, aims to identify parking management options and sustainable transportation alternatives that could be implemented in the Meech Lake sector of Gatineau Park to address parking shortages at Parking Lot 13 during the busy summer season. Four alternative parking and transportation strategies are considered: variable rate parking fees; time-managed entry reservation systems; active modes of transportation; and the exploration of a shuttle bus service expansion. Each approach is examined based on its advantages, limitations and public perceptions. The purpose of this study is to help inform Gatineau Park’s managerial team of the most efficient means of managing visitor use of Parking Lot 13 at Meech Lake with minimal pushback from the public to sustain current recreational activities and provide a safe and high-quality visitor experience.